Delivering an intervention to a young person minimising his harmful sexual behaviour – a practice case study. Issue 2 (4th May 2019) - Hatton, Victoria Anne; Duff, Simon
ABSTRACT: Young perpetrators of harmful sexual behaviour (HSB) often minimise the severity of their offending. Whilst there have been mixed findings, the most recent literature suggests offence-specific minimisation increases the risk of sexual recidivism in high risk sexual offenders. The presented case study summarises the authors' engagement with a 17-year-old perpetrator of internet-related HSB (arrested for possessing and distributing thousands of indecent photographs of children) who was minimising the severity of his offending. The client engaged in a six-session intervention which was adapted from two HSB manuals. This involved exploring minimisation, perspective taking and HSB consequences. To assist the formulation process and evaluate the effectiveness of the intervention, the Internet Behaviour and Attitudes Questionnaire was administered and an unstructured interview facilitated. Whilst the IBAQ revealed a slight increase in minimisation, the interview demonstrated developments in the client's insight into his offending. Implications for future research and practice development are discussed.